PEMBERDAYAAN MASYARAKAT MELALUI PENYULUHAN PARTISIPATIF: UPAYA PENINGKATAN KEMANDIRIAN EKONOMI WARGA DI DESA BANYUKAPAH KECAMATAN KEDUNGDUNG KABUPATEN SAMPANG - Moh. Rodiaminollah; Moh. Ali Fahmi (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Banyukapah Village, located in Kedungdung District, Sampang Regency, possesses significant agricultural and livestock potential. However, the level of economic self-reliance among its residents remains relatively low. Most community members depend on middlemen and sell raw products without added value. This community service program aimed to enhance the economic self-reliance of local residents through participatory extension activities initiated in collaboration with the Nahdlatul Ulama (NU) Branch Organization of Banyukapah. The method employed was participatory extension, consisting of several stages: coordination, focus group discussions (FGDs) to identify community problems, implementation of two extension sessions, hands-on practice, and one month of mentoring. The target participants were 38 residents of Banyukapah Village, including members of the NU branch organization, PKK women's group members, and youth organization representatives. The results demonstrated significant improvements: (1) 76% of participants were able to calculate the Cost of Production (COP) and business profits; (2) three new business groups were established, namely “NU Banyukapah Mandiri” for cassava-based products, “Barokah Farm” for honey production, and “Santri Tani” for organic fertilizer production; and (3) five residents began utilizing social media for product marketing. The study concludes that participatory extension based on collaboration with the NU branch organization is effective in improving community knowledge, skills, and economic self-reliance practices, supported by strong social trust and cultural proximity. For sustainability, it is recommended to strengthen the economic division within the NU branch organizational structure and allocate Village Funds for advanced training programs and revolving capital support